Staging during anion-exchange intercalation into [LiAl2(OH)6]Cl.yH2O: structural and mechanistic insights. - Williams, G; Fogg, A; Sloan, J; Taviot-Guého, C; O'Hare, D (2007)
A series of experiments has been performed to seek more insight into the staging process that occurs during anion-exchange intercalation of some organic carboxylates and phosphonates into the layered double hydroxide [LiAl2(OH)6]Cl.yH2O. High resolution transmission electron microscopy has been employed to gain additional insight into the second-stage intermediates, providing strong evidence that the Rüdorff model of staging is applicable. Small-angle X-ray scattering was used to study the very early stages of the intercalation of succinate into [LiAl2(OH)6]Cl.yH2O: it was observed that the only species present during the reaction were the host, a second-stage intermediate and the first-stage product. The influence of temperature and solvent on the reaction mechanism was investigated. Staging was observed only at low temperatures (T<60 degrees C), and found to be confined largely to aqueous systems. Reactions performed in a 95:5 (v/v) mixture of water and a second non-aqueous solvent such as ethanol, acetone, THF or formamide proceeded via a second-stage intermediate, whereas for those undertaken in 50:50 (v/v) mixtures a direct transformation from host to product was usually observed.